2014
DOI: 10.1007/s00228-014-1700-3
|View full text |Cite
|
Sign up to set email alerts
|

α1-Adrenergic receptor antagonists and gynecomastia. A case series from the Italian spontaneous reporting system and VigiBase™

Abstract: In this study, we highlight a possible association between gynecomastia and tamsulosin use. To our knowledge, this association has not been described before and could represent a potential signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The patient was also taking tamsulosin, a potential cause of gynecomastia. 3 However, gynecomastia did not recur when he was no more exposed to atorvastatin even though tamsulosin was continued. It is also unlikely that the androgen-receptor abnormalities caused by the previous treatment with bicalutamide could be present many years later and play a role in the development of gynecomastia.…”
Section: To the Editormentioning
confidence: 96%
“…The patient was also taking tamsulosin, a potential cause of gynecomastia. 3 However, gynecomastia did not recur when he was no more exposed to atorvastatin even though tamsulosin was continued. It is also unlikely that the androgen-receptor abnormalities caused by the previous treatment with bicalutamide could be present many years later and play a role in the development of gynecomastia.…”
Section: To the Editormentioning
confidence: 96%
“…In summary, to make the best use of available resources, detected SDRs require clinical review of the reports (Wisniewski et al, 2016). Examples of works that combine DA with a clinical review of reports may be found (de Jong et al, 2012;Tarapués et al, 2013;Viola et al, 2014;Béné et al, 2016;Valdiserra et al, 2023).…”
Section: Signals Signals Of Disproportionate Reporting and Risksmentioning
confidence: 99%
“…New member countries developed PV centers to report the ADRs and coordinate with the WHO center in Uppsala, where VigiBase is based. VigiBase contains more than 8 million ADR reports from more than 110 countries 62 . VigiFlow is an internet-based system that offers free access to all member countries to see all information and reports in VigiBase, and their analysis from all over the world 63 .…”
Section: Policies and Procedures For Implementing Pharmacovigilancementioning
confidence: 99%